'In the tomb of Ser Piero': death and burial in the family of Leonardo da Vinci. Issue 3 (27th January 2016) - Leader, Anne
Abstract : The origins of Leonardo da Vinci (1452–1519) have fascinated scholars for well over a century. Archival research has revealed much about Leonardo's origins and his complex family that included four stepmothers and twenty‐three half‐brothers and half‐sisters and their offspring. One source, however, has been overlooked by scholars – a Libro dei defunti, or necrology, kept by the Benedictine monks of the Badia Fiorentina, where Leonardo's father installed a family tomb in the late fifteenth century. This book of the dead, which lists burials from 1499 through the late eighteenth century, not only offers precious information about which of Leonardo's relatives found their final rest in Florence at the Badia but also provides invaluable help in reconstructing the disposition of the church interior. This article traces the history of the Da Vinci tomb from its first burial in 1474 to its last in 1614 and provides a transcription and analysis of relevant notices found in the Badia's Libro dei defunti.